Analisis Pengaruh Ketersediaan Produk Halal, Harga Dan Kualitas Produk Terhadap Loyalitas Pelanggan Di Assalam Hypermart Sukoharjo - Nurohman, Muhammad Iqbal; , Soepatini, S.E., M.Si., Ph.D (2015)
The purpose of this study is to analyze the influence of halal product assortment, price, and product quality on Assalaam Hypermart customer loyalty. Besides that, this study also tries to analyze the meaningfulness of the model in explaining customer loyalty. This study hopefully can deepen knowledge regarding to customer loyalty and can be made as a reference to future studies. The hypothesis of this study is it is expected that halal product assortment, price, and product quality significantly influence customer loyalty. It is also expected that the model can explain customer loyalty meaningfully. The population of this study is customer of Assalaam Hypermart. The sampling method used is convenience sampling with 40 respondents taken into account. This study employs multiple regression test (t test, F test, and R2 test) Conclussions are drawn from this study. It is concluded that halal product assortment does not significantly influence customer loyalty, neither does price. On the other hand, it is concluded that product quality significantly influences customer loyalty. Finally, this study concludes that halal product assortment, price, and product quality is a model that can explain customer loyalty meaningfully. This study suggests Assalaam Hypermart to manage its meats line product more carefully, and to manage its product assortment more thoroughly.